Study Of Learning Opportunities And Challenges Based On Digital Pandemic Era - Kaharuddin Kaharuddin; Iskandar Iskandar; Ansurlawarlin Ansurlawarlin; Muh. Nur Alfin Zahar; Nuramal Nuramal (Indonesian Journal Publisher, 2022)
This article will discuss digital-based learning across subjects at all levels of educational institutions as a learning media tool. The discussion of digital-based learning is a very fundamental part to be understood by all educators, both at the school level and at the university level. This article is a literature review with a qualitative analysis knife method that explores in depth related to digital-based learning across subjects at various levels of education. Furthermore, digital-based learning for educators holistically is an obligation in mastering digitalization in the learning process because all materials or subjects at all levels of education are very in tune with technology. Based on the findings from the literature review results in various subjects and levels of education, digitalization in learning has increased student learning achievement. On average, educators who use digital-based learning across subjects encourage student achievement. But on the other hand, a phenomenon was also found, including students experiencing digital addiction for those who use cellphones, some teachers still have difficulty in digital-based learning, facilities for digital learners have not become full attention, internet access is limited, digital media innovation has not been maximized. Therefore, through this article, it is hoped that all educators such as teachers and lecturers will be more creative and explore the use of digital-based learning media that are more sophisticated and attractive so that students are more motivated in the learning process, so that student achievement continues to increase.